Analysis of Proposed Waste Management Strategies at XYZ Islamic Boarding School Using SWOT and Promethee - Wesha, Defi Milenia Putri; Rimantho, Dino (Jurnal Teknologi, 2024)
As a country with a population of 261,115,456 people, Indonesia produces 65 million tons of waste per year. This large amount of waste is not matched by good waste management. Improving waste management must be done from the source, one of which is the XYZ boarding school.  Thus, this study aims to determine the waste management strategy to improve waste management at the XYZ Islamic Boarding School. The determination of the process was carried out using the SWOT and Promethee methods. Based on the SWOT analysis results, alternative waste management strategies that can be implemented at the XYZ Islamic Boarding School are known. Furthermore, these alternatives are analyzed again to determine which options will be prioritized using the Promethee method. The results show that XYZ Islamic Boarding School can implement the SO strategy with a value of 4,830, and the priority strategies are conducting waste management training by trainers or teachers to employees of the boarding school, building waste management facilities in the boarding school area, and building good cooperation with waste management institutions.